A construção/desconstrução da subjetividade a caminho de uma identidade singular - Pismel, Maria Claudia de Chiara (2010)
The central idea of this study is the psychosocial analysis of subjectivity in the neoliberal consumer society. The objective is to demonstrate the ideological domination in the "construction / deconstruction of subjectivity under the contingencies of neoliberal consumer society, to build / individuals to be standardized, without autonomy and delivered to the determinations of the market, deconstructing / hindering the construction of a singular subjectivity. We will present the historical changes that nurture the emergence of neoliberal society of consumption, the main features of it and its mode of action / transformation of subjectivity. We emphasize the analysis of Critical Theory regarding the mechanisms of ideological domination, as the culture industry and its impact on the formation and maintenance of individuals in the mass condition of standart consumer, but capable of emancipation. We will present the identification process as constitutor of subjectivity, an instrument in favor of ideology or in favor of potentiality transformation.